Assessment of Solid-State Behaviour and in vitro Release of Artemether from Liquisolid Compact Using Mesoporous Material as an Excipient - Manjunath, Archana; Bhattacharyya, Sayani (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Artemether is a potent antimalarial drug used in the first-line treatment of multi-drug-resistant malaria. It belongs to BCS II, exist in different polymorphic forms, and exhibits incomplete absorption and low oral bioavailability owing to poor dissolution. Aim: The present study evaluates the effect of different mesoporous materials in the liquisolid compact for the augmentation of dissolution of the drug, and polymorphic stability. Materials and Methods: In the liquisolid compact Tween 80 was used as a non-volatile solvent for the dispersion of the drug, microcrystalline cellulose as carrier, and Syloid244FP and SyloidXDP as coating materials at different coating and carrier ratios. Eight such formulations were prepared. The formulated liquisolid compact was evaluated for precompression parameters, followed by direct compression process. The tablets thus prepared were assessed for hardness, friability, wetting time, in-vitro dissolution, and stability studies. Physico-chemical characterization was done to study drug excipient interaction, thermal behaviour, and surface characteristics. Results and Discussion: The study revealed that an increasing quantity of mesoporous material exhibited a better release profile compared to the pure drug. Good compressibility and tablet ability were observed at a carrier and coating materials ratio of 1:5. Compatibility between the drug and excipients was established from the FTIR study. Noteworthy findings of PXRD and DSC suggested the presence of artemether in metastable β form in the formulations. Short-term stability of the formulations was established. Conclusion: Hence, the approach of liquisolid compact using mesoporous silicas at a suitable excipient ratio could be an optimistic approach for the enhancement of dissolution and stability of artemether.
Keywords: Artemether; Liquisolid compact; Solid-state behaviour; Dissolution; Mesoporous silica